Characterisation of Pain Responses in the High Fat Diet/Streptozotocin Model of Diabetes and the Analgesic Effects of Antidiabetic Treatments - Frederika Maria Byrne; Sharon Cheetham; Steven Vickers; Victoria Chapman (Journal of Diabetes Research)
Chronic pain is a common complication of diabetes. The aim of the present study was to characterise pain behaviour in a high fat diet/streptozotocin (HFD/STZ) model of diabetes in the rat, investigate spinal mechanisms, and determine the effects of antidiabetic interventions. Three-week consumption of a high fat diet followed by single injection of STZ (45 mgkg−1) produced sustained changes in plasma insulin and glucose until day 120. Hindpaw mechanical withdrawal thresholds were significantly lowered in the model, but mechanically evoked responses of spinal neurones were unaltered, compared to HFD/vehicle rats. HFD/STZ rats had significantly lower numbers of spinal Iba-1 positive cells (morphologically identified as activated microglia) and spinal GFAP immunofluorescence (a marker of astrogliosis) in the spinal cord at day 50, compared to time-matched controls. The PPARγ ligand pioglitazone (10 mgkg−1) did not alter HFD/STZ induced metabolic changes or hindpaw withdrawal thresholds of HFD/STZ rats. Daily linagliptin (3 mgkg−1) and metformin (200 mgkg−1) from day 4 after model induction did not alter plasma glucose or insulin in HFD/STZ rats but significantly prevented changes in the mechanical withdrawal thresholds. The demonstration that currently prescribed antidiabetic drugs prevent aberrant pain behaviour supports the use of this model to investigate pain mechanisms associated with diabetes.